Gestión del control interno para inventarios en fábricas hormigoneras - Sánchez Lino, Ana Patricia (2021)
The present research work consists of improving the processes in the management of internal control for inventory of concrete manufacturing companies; and in turn make a correct record of inventory movements in the accounting books. However, the concrete mixer company under study does not have an efficient internal control management system, causing deficiencies in the material inventory. For that reason, the question in formulating the problem is to know how does the incorrect internal control in the inventory affect the profitability of the companies dedicated to the production of concrete? and as a means to obtain information on the problem encountered, it was considered to apply the following instruments: interview, direct observation and documentary information, providing as a result that the company under study lacks policies and procedures manuals for internal inventory control. The application of the policies and procedures manuals will help management and shareholders to have efficient and reasonable information, evaluate business..........